Analysis Of Operational Cost Control From The Cashier's Perspective Using The Sapta Hemat Program - Cahyati, Desi; Fatihah, Dian Candra (Transforma Jurnal Manajemen, 2025)
This article is entitled Analysis of Operational Cost Control from the Cashier's Perspective Using the Sapta Hemat Program. This study aims to describe the role of cashiers in implementing the Sapta Hemat program at Sagaracipta Minimarket. The Sapta Hemat program is a retail company policy that aims to reduce operational costs   through savings in 7 aspects, namely; saving electricity, saving water, saving promotional costs, saving stationery, saving SHB (plastic), saving others and saving BTK. The research method used is descriptive qualitative, with data collection techniques through observation, in-depth interviews and documentation. Cashiers have an important role in implementing Sapta Hemat, both as direct implementers and as reminders for coworkers and customers. Cashiers actively educate consumers regarding plastic savings and maintain daily work efficiency. However, the implementation of plastic saving still faces obstacles, because most consumers have not brought their own shopping bags and are not fully aware of the policy. This study concludes that the success of Sapta Hemat is strongly influenced by the active participation of cashiers and support from consumers. Therefore, additional strategies are needed such as providing affordable alternative bags and increased education to customers. Keyword: Operational cost control, Cashier, Plastic, Sapta Hemat, Minimarket